Dengue Outbreak in Peshawar: Clinical Features and Laboratory Markers of Dengue Virus Infection - Muhammad Haroon; Hasnain Jan; Shah Faisal; Nasir Ali; Muhammad Kamran; Farhan Ullah (Elsevier, 2019)
Background: Dengue is a tropical disease caused by dengue virus (DENV). It is one of the most significant arthropod-borne viral infection. Objectives: The aim of the current study was to characterize epidemiological, clinical features and laboratory markers of dengue infection during the recent epidemic in Peshawar, KP. Methods: During the prospective hospital-based observational study, 2000 dengue suspected cases were serologically examined at Lady Reading Hospital (LRH) Peshawar. Dengue NS1 antigen and Dengue IgG and IgM antibody ELISA tests were conducted for the confirmation of dengue infection. Data regarding the clinical features, platelet count and liver function tests were also recorded for the dengue positive patients. Results: Out of total samples 415 (21%) cases including 309 (74%) male and 106 (25%) female were detected positive for the dengue infection. In the dengue positive patients, the highest prevalence was observed in the age group of 21-40 years with 160 (38%) followed by the age group of 1-20 years with 89 (21%) patients. Fever was recorded in 100% of the dengue patients followed by a headache and fatigue in 73% and liver abnormality observed in 70% of the cases. During laboratory examinations IgM antibody was detected in 180 cases, followed by IgG antibody in 87, NS1 antigen in 43, NS1 antigen along with IgG and IgM antibodies in 41 dengue positive cases. Another combine detection of NS1 antigen with IgM antibody, NS1 antigen with IgG antibody and both IgG and IgM antibodies was observed in 21, 21, 22 dengue cases respectively. Conclusion: It was concluded that the dengue infection can be early diagnosed on the basis of described clinical features and with the detection of dengue-specific NS1 antigen along with antibodies such as IgG and IgM. Keywords: Dengue, Epidemic, Clinical features, Laboratory markers